Effects and moderators of coping skills training on symptoms of depression and anxiety in patients with cancer: Aggregate data and individual patient data meta-analyses. (August 2020) - Buffart, L.M.; Schreurs, M.A.C.; Abrahams, H.J.G.; Kalter, J.; Aaronson, N.K.; Jacobsen, P.B.; Newton, R.U.; Courneya, K.S.; Armes, J.; Arving, C.; Braamse, A.M.; Brandberg, Y.; et al.
Abstract: Purpose: This study evaluated the effects of coping skills training (CST) on symptoms of depression and anxiety in cancer patients, and investigated moderators of the effects. Methods: Overall effects and intervention-related moderators were studied in meta-analyses of pooled aggregate data from 38 randomized controlled trials (RCTs). Patient-related moderators were examined using linear mixed-effect models with interaction tests on pooled individual patient data ( n  = 1953) from 15 of the RCTs. Results: CST had a statistically significant but small effect on depression (g = −0.31, 95% confidence interval (CI) = −0.40;-0.22) and anxiety (g = −0.32, 95%CI = -0.41;-0.24) symptoms. Effects on depression symptoms were significantly larger for interventions delivered face-to-face ( p  = .003), led by a psychologist ( p  = .02) and targeted to patients with psychological distress ( p  = .002). Significantly larger reductions in anxiety symptoms were found in younger patients (pinteraction  < 0.025), with the largest reductions in patients <50 years (β = −0.31, 95%CI = -0.44;-0.18) and no significant effects in patients ≥70 years. Effects of CST on depression (β = −0.16, 95%CI = -0.25;-0.07) and anxiety (β = −0.24, 95%CI = -0.33;-0.14) symptoms were significant in patients who received chemotherapy but not in patients who did not (pinteraction  < 0.05). Conclusions: CST significantly reduced symptoms of depression and anxiety in cancer patients, and particularly when delivered face-to-face, provided by a psychologist, targeted to patients with psychological distress, and given to patients who were younger and received chemotherapy. Highlights: The average effect of CST on symptoms of anxiety and depression in cancer patients are statistically significant but small Younger patients and patients who received chemotherapy benefit more from CST CST effects are larger when delivered face-to-face, led by a psychologist and targeted to patients with psychological distress